Letter - Roberts, Wilfrid
037-0164-001 COMMITTEE FOR SPANISH REFUGEE CHILDREN NORTH STONEHAM CAMP NORTH STONEHAM EASTLEIGH :: HANTS :: TELEPHONE: CHANDLERSFORD 353 ALL CORRESPONDANCE TO BE ADDRESSED TO THE ADMINISTRATION 28th May, 1937. Dear Mr. Tewson, David Grenfell tells me that you were a little surprised that you were not invited to the meeting on Wednesday. This was our ordinary routine meeting of the National Joint Committee, and a number of questions quite apart from the Basque children were discussed. The matter of the Canp did come up at the end, and I made a report on what the situation was. I do not think I informed my Committee of anything of which you were not already aware and we came to no decision with regard to any question concerning the children from the Camp. I feel it was quite right for me to have given this report and that it would have been wrong not to have allowed my Committee to discuss this very urgent problem. We have provisionally arranged, subject to your approval a meeting of the Basque children's Committee for Monday, May 31st at 3.30 and I hope this will be convenient to you. You will be receiving an official notification from Mrs. Miller. I was very sorry indeed that I myself missed Miss Sutherland and Mr. Harris the other day, when they were here, though Mr. Brinton saw them. I may report that the whole situation here is very much improved. I have great confidence in Mr. Brinton's organising capacity and have watched the progress in the last five days, when magnificent improvements have been made under very difficult circumstances. I am glad to report that the distribution of food has now been put on a satisfactory basis. Yours sincerely, Wilfrid Roberts 292/946/37/164